Teacher-developed modules on communicable diseases and student learning outcomes - Reyes, Grace Leus (2005)
The effects of three developed learning modules on disease prevention and control with the topics of communicable diseases, herbal medicines and non-communicable diseases were investigated and validated in an experimental and control group. Results showed that all three modules in Disease Prevention and Control are valid. The students who used the learning modules on Disease Prevention and Control had higher scores in the posttest as compared to the students who used the Textbook-Centered Teacher Directed Format prescribed by the Department of Education. Also, the use of learning modules enriched health instruction.
"April 2005."
Thesis (M.A. Education : Health Education)--University of the Philippines Diliman.
Keywords: Health education (Secondary) -- Philippines -- Bulacan; Communicable diseases -- Study and teaching (Secondary) -- Philippines -- Bulacan; Teaching -- Philippines -- Bulacan -- Aids and devices